Blended Learning in Nursing Education: A Pilot Study on the Role of Resilience and Self-Confidence in Achieving Learning Outcomes - Luis Figo Febriano; Rustiana Tasya Ariningpraja; Retno Lestari; Muhammad Rizky Adipratama; Umi Maghfiroton Fitri (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
This cross-sectional study examined the roles of resilience and self-confidence in supporting academic success within blended learning environments in undergraduate nursing education. Blended learning combines face-to-face instruction with digital delivery, demanding high levels of adaptability and self-regulated learning from students. Data were collected from 146 nursing undergraduates enrolled in blended courses across multiple universities. Validated instruments—the Resilience Assessment Questionnaire (RAQ-8) and the Trait Measure of Robustness of Self-Confidence—were culturally adapted and administered. Grade Point Average (GPA) was used as an indicator of academic achievement. Descriptive statistics, Mann–Whitney U tests, and correlation analyses were conducted to evaluate associations among key variables. Results showed a robust positive correlation between resilience and GPA (p < .001), underscoring the importance of persistence and adaptability for learning outcomes. Self-confidence likewise demonstrated a significant, beneficial association with academic performance, supporting proactive engagement and buffering the effects of setbacks. A complementary relationship between resilience and self-confidence was also observed, suggesting that these attributes, when combined, may enhance their collective contribution to academic success. These findings underscore the importance of targeted educational strategies—such as mentoring, structured feedback, and guided reflection—to enhance psychological resilience and self-assurance. Integrating such supports into blended curricula may better equip nursing students to navigate academic and clinical demands and enhance their readiness for professional practice.